Evolution 2.0
XII, 264 p.
Keywords: These essays by leading philosophers and scientists focus on recent ideas at the forefront of modern Darwinism, showcasing and exploring the challenges they raise as well as open problems. This interdisciplinary volume is unique in that it addresses the key notions of evolutionary theory in approaches to the mind, in the philosophy of biology, in the social sciences and humanities; furthermore it considers recent challenges to, and extensions of, Neo-Darwinism. The essays demonstrate that Darwinism is an evolving paradigm, with a sphere of influence far greater than even Darwin is likely to have imagined when he published ‘On the Origin of Species’ in 1859.